Co-developing a Mental Health and Wellbeing Chatbot With and for Young People - Grové, Christine (Frontiers in Psychiatry, 2021)
There are many young people who experience mental health and wellbeing challenges. A potential negative mental health trigger for some youth is a struggle to cope with stress at school, feelings of depression and anxiety and availability of adequate help for these stressors. In response to youth needs a mental health and wellbeing chatbot has been co-developed with youth, technology partners and expert stakeholders. An element of the chatbot is powered by artificial intelligence and rules based AI using natural language processing. It is created to communicate evidence based resources, wellbeing support, educational mental health information and adaptive coping strategies. This paper will discuss how the chatbot has been developed, highlighting its participatory, co-design process with youth who are the key stakeholders to benefit from this digital tool. Research from interviews and surveys informed the creation of the chabots personality and its character design. Examples of the conversation design and content development are provided. The paper finishes with how, if at all, digital tools such as chatbot applications could support the mental health of young people in secondary schools or health care settings in conjunction with the wellbeing or health care team, concluding with lessons learned and cautions.